Capital Market Reaction To The Announcement Of Fuel Price Increase On Stock Returns Of Lq 45 Transportation Sub-Sector In 2023 - Erlina Erlina; Nelly Meinissa Azahra; Acep Komara (Jurnal Ekonomi Teknologi dan Bisnis (JETBIS), 2024)
The research was conducted to find out the reaction of the capital market to the rise in BBM in transportation and logistics sector companies listed on the Indonesian Stock Exchange. This study is an event study or event that arises directly from the rise in the price of oil (BBM) on October 1, 2023, against the market reaction based on the actions of transportation and logistics companies. Abnormal Return and Trading Volume Activity are variables used to analyze reactions. The data collection method used in this research is the Quantitative Data Method. Observations were conducted for 5 days before and 5 days after the BBM rise on October 1, 2023, using the Wilcoxon Signed Ranks test with a sample of 10 companies and a data test of 110. On the test results, there were abnormal differences in return and trading volume activity before and after the rise in BBM prices, the results could help market participants understand market dynamics, find investment opportunities, and manage risk. With a rise in sales, this means investors respond to events so that the markets react. The findings support the theory of signals because investors see the announcement of a BBM rise as a signal that can affect the stock price.